C-Fos, ΔFosB, BDNF, trkB and Arc Expression in the Limbic System of Male Roman High- and Low-Avoidance Rats that Show Differences in Sexual Behavior: Effect of Sexual Activity. (1st January 2019) - Sanna, Fabrizio; Poddighe, Laura; Serra, Maria Pina; Boi, Marianna; Bratzu, Jessica; Sanna, Francesco; Corda, Maria Giuseppa; Giorgi, Osvaldo; Melis, Maria Rosaria; Argiolas, Antonio; Quartu, Marina
Highlights: Male Roman High- (RHA) and Low-Avoidance (RLA) rats display significant differences in sexual behavior. These differences occur with changes in cFos, ΔFosB, BDNF, trkB and Arc expression in limbic brain areas of both rat lines. Changes are more evident in RHA than RLA rats after the first and tend to disappear after five copulatory tests. Sexual activity causes neural activation and synaptic plasticity depending on sexual experience level and genotype/phenotype. Abstract: Male Roman High- (RHA) and Low-Avoidance (RLA) rats display significant differences in sexual behavior (RHA rats exhibit higher sexual motivation and better copulatory performance than RLA rats). These differences are very evident in sexually naïve rats (which copulate with a receptive female rat for the first time), and are still present, although reduced, after five copulatory tests, when sexual experience has been acquired. Since sexual activity is a natural reward that induces neural activation and synaptic plastic changes in limbic brain areas, we studied whether the differences in sexual activity between these rat lines are accompanied by changes in the expression of markers of neural activation and plasticity, i.e., c-Fos, ΔFosB (a truncated form of FosB), Brain-Derived Neurotrophic Factor (BDNF) and its tyrosine kinase receptor B (trkB) and Activity regulated cytoskeleton-associated (Arc) protein in the ventral tegmental area (VTA), nucleus accumbens (Acb) (core and shell) and medial prefrontal cortex (mPFC) of sexually naïve and experienced RHA and RLA rats by Western Blot and/or immunohistochemistry. This study shows that these markers changed differentially in the VTA, Acb and mPFC of RHA and RLA rats, after sexual activity. In both rat lines, the changes were very evident in naïve rats, tended to disappear in experienced rats and were higher in RHA than RLA rats. These findings confirm that sexual activity induces neural activation in limbic brain areas involved in motivation and reward, leading to changes in synaptic plasticity with sexual experience acquisition, and show that these depend on the animals' genotypic/phenotypic characteristics.